Analysis Function Human Resource Management: Recruitment, Training, Career Development, Industrial Relation - Anggia Rettrisunz PIM Panjaitan; Didin Sjarifudin; Nuraeni; Josua Panatap Soehaditama; Agustian Zen (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this manuscript is to search the literature to support the variables of this manuscript and to provide results for consideration in future studies as a research gap or alongside other research items. This study did not use SPPS data processing and there were no study participants. Results were obtained. Most of the articles reviewed in the scientific literature had a significant impact on the independent variable of the dependent variable. New to this study is the existence of models or frameworks that previously existed or were used by previous researchers.